Rare case of red tears: ocular vicarious menstruation. Issue 3 (9th March 2021) - Ghosh, Soumitra; Tale, Sudheer; Handa, Neha; Bhalla, Ashish
Abstract : Bloody tears or haemolacria is a rare clinical entity. It is caused by various ocular and systemic conditions. Haemolacria due to vicarious menstruation is even rarer. In this article, we presented a case of cyclical episodes of bloody tears coinciding with menstrual cycle in a 25-year-old married female patient. Extensive physical, ophthalmological and radiological evaluation failed to reveal other potential causes of her complaint. A diagnosis of ocular vicarious menstruation was made and she was treated with oral contraceptive pills. No such episode recurred during 3 months follow-up period.